Analysis of Outcomes in Living Donor Liver Transplants Involving Reconstructive Microsurgeons - Hernandez, Jorge Andres; Mullens, Cody L.; Aoyama, Julien T.; Ligh, Cassandra A.; Shaked, Abraham; Olthoff, Kim M.; Abt, Peter L.; Levin, L. Scott; Kovach, Stephen J., III (Journal of Reconstructive Microsurgery, 2020)
Background Living donor transplantation is becoming increasingly popular as a modality for patients necessitating liver transplantation. Hepatic artery thrombosis (HAT) remains the most feared acute postoperative complication associated with living-donor liver transplantation. Preoperative planning, including scheduling reconstructive microsurgeons to perform the hepatic artery anastomosis using a surgical microscope or loupes, can decrease HAT rates.Methods A retrospective review of two reconstructive microsurgeons at a single institution was performed to analyze postoperative outcomes of adult and pediatric live donor liver transplants where reconstructive microsurgeons performed the hepatic artery anastomosis. One surgeon utilized the surgical microscope, while the other surgeon opted to use surgical loupes for the anastomosis.Results A total of 38 patients (30 adult and eight pediatric) met inclusion criteria for this study, and average patient age in the adult and pediatric population studied was 48.5 and 3.6 years, respectively. Etiologies of adult patients' liver failure were most commonly cholestatic (43%), followed by alcohol (23%), hepatitis C virus-related cirrhosis (17%), and nonalcoholic steatohepatitis (7%), while etiologies of pediatric liver failure were most commonly cholestatic (62.5%). None of the patients (0%) experienced acute postoperative HAT. On average, 22 and 25 months of postoperative follow-up was obtained for the adult and pediatric cohorts, respectively, and only one adult patient was found to have any liver-related complication.Conclusion A collaborative relationship between reconstructive microsurgeons and transplant surgeons mitigates the risk of HAT and improves patient outcomes in living donor liver transplantation.
Keywords: liver transplant; living donor liver transplantation; microsurgery; hepatic artery thrombosis; plastic surgery